The Association Between Asymmetrical Hallux Valgus and Lumbar Spine Deformities: An Analysis from the Large General Population Cohort - Takumi Matsumoto MD PhD; Ryutaro Takeda MD, PhD; Sakae Tanaka MD PhD (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Bunion Introduction/Purpose: Various factors contribute to hallux valgus (HV), including footwear, genetics, gender, anatomical factors, and joint laxity. Theoretically, these factors should affect both sides equally, yet overwhelmingly, bilateral cases are more common. Although rare, there are instances of unilateral cases or cases with significant asymmetry between the left and right sides. However, there is a lack of systematic investigation into the background of such cases. Methods: Data from the fifth survey of the Osteoarthritis/Osteoporosis Against Disability (ROAD) study, a nationwide prospective study in Japan, were analyzed. HV severity was categorized into 4 grades based on the radiographic HV angle, and asymmetric HV was defined as having at least one HV on either side with a difference of two or more severity grades between the left and right. Controls were matched from both the normal group (without HV on both sides) and the symmetric group (HV on at least one side with a difference of one or less severity grades). Univariate analysis assessed lumbar conditions, and multinomial logistic regression analysis explored the association between lumbar spine disorders and asymmetric HV. Results: Among 1,231 participants, 27 (2.2%) had asymmetric HV. The asymmetrical group showed a significantly higher prevalence of L5 spondylolisthesis and scoliosis (asymmetrical vs symmetrical vs normal: [L5 spondylolisthesis] 15% vs 5% vs 1%, p = 0.0178; [scoliosis] 42% vs 20% vs 14%, p = 0.0095). The results of the multiple logistic regression analysis revealed that the odds ratios for asymmetry, with normal as the reference, were 3.59 (95% CI: 1.11-11.58) in the presence of scoliosis and 6.98 (95% CI: 0.67-72.60) in the presence of L5 spondylolisthesis. Conclusion: Unilateral HV has been reported as a complication following spinal surgery. This study establishes a link between lumbar spine scoliosis and unilateral HV. It suggests the involvement of factors such as impairment of the hallux abductor muscle's innervating nerves or left-right load imbalance in the development of unilateral HV deformities.